IMPROVING FINANCIAL LITERACY IN MSMES THROUGH BOOKKEEPING TRAINING AND LITERACY EDUCATION - Hakima Maris; Ratih Kusumastuti; Muthmainah Mursidin; Hendra Railis; Dada Suhaida; Yuliana Yuliana (International Journal of Engagement and Empowerment, 2022)
MSMEs  are expected to   be the forefront to strengthen economic pillars  in achieving  sustainable development goals (SGDs). This is  because MSMEs   are  one of the most able businesses to survive in deteriorating economic conditions, especially in this Covid-19  pandemic. Therefore    , MSMEs must have good financial management so that the business carried out can be  sustainable. One of them is by   having the correct financial record and compiling the financial statements needed to make   decisions in planning the next business strategy. Food MSMEs  in Indonesia do not have a good record, so they cannot produce financial statements. The results  of training and mentoring make simple bookkeeping and compile these financial statements  increase the awareness of MSME  actors for the importance of information generated by financial  statements. as the basis for decision making  and preparing business strategies  to achieve sustainable  business